2017
DOI: 10.1002/jat.3476
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications and human biosafety of nanomaterials used in nanomedicine

Abstract: With the rapid development of nanotechnology, potential applications of nanomaterials in medicine have been widely researched in recent years. Nanomaterials themselves can be used as image agents or therapeutic drugs, and for drug and gene delivery, biological devices, nanoelectronic biosensors or molecular nanotechnology. As the composition, morphology, chemical properties, implant sites as well as potential applications become more and more complex, human biosafety of nanomaterials for clinical use has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(79 citation statements)
references
References 264 publications
(240 reference statements)
0
78
0
1
Order By: Relevance
“…This highlights the versatility of a nanocrystal drug platform. Pharmacokinetic, biodistribution, and bioavailability data for organs involved in delivery routes tested using nanocrystal technology have been addressed at length previously . Specifically, the reviews of Lu et al 2016 and 2017 delve into the biodistribution pattern of nanocrystal drugs in the blood, heart, liver, spleen, lung, kidney, tumor, and thymus (i.e., the organs involved in clearance/circulation and host immune responses) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the versatility of a nanocrystal drug platform. Pharmacokinetic, biodistribution, and bioavailability data for organs involved in delivery routes tested using nanocrystal technology have been addressed at length previously . Specifically, the reviews of Lu et al 2016 and 2017 delve into the biodistribution pattern of nanocrystal drugs in the blood, heart, liver, spleen, lung, kidney, tumor, and thymus (i.e., the organs involved in clearance/circulation and host immune responses) …”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic, biodistribution, and bioavailability data for organs involved in delivery routes tested using nanocrystal technology have been addressed at length previously. 10,13,18,24,25,[29][30][31][32][33][34] Specifically, the reviews of Lu et al 2016 and 2017 delve into the biodistribution pattern of nanocrystal drugs in the blood, heart, liver, spleen, lung, kidney, tumor, and thymus (i.e., the organs involved in clearance/circulation and host immune responses). 24,35 Several articles have been published, discussing the techniques used to synthesize nanocrystal drugs; the type of stabilizers or surfactants involved; and the methods adopted for physicochemical and biological characterization.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of nanotechnology, potential applications of nanomaterials in medicine have been researched widely in recent years. 1 Nanomaterials have developed rapidly, and traditional nanomaterials are now unable to meet the needs of some special industries or high technology. Multifunctional Janus nanoparticles (NPs) have become a hot spot in the research field of nanomaterials in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…However, since most clinical research reports for nanomedicine products focus mainly on the therapeutic efficacy of drugs, human biosecurity information is limited. In order to evaluate the human biosafety of nanomedicine products in clinical studies, it has been reported that a standardized test battery should be developed, including all indices of blood chemistry, carcinogenic, teratogenic, mutagenic toxicities and immune, nervous and reproductive systems (12).…”
Section: Anahtar Kelimelermentioning
confidence: 99%